Letter (copy) : Capture of two British nationals in Madrid - Citrine, Walter, 1887-1983
010-0059-001 WMC/HVT/FC/201. Secretary's. BY HAND. 9th November, 1936. The Rt. Hon. Anthony Eden, M.P., Secretary of State for Foreign Affairs, The Foreign Office, Downing Street, S.W.1. Dear Mr. Eden, CAPTURE OF TWO BRITISH NATIONALS IN MADRID. I have this morning received a telegram from a prominent Trade Unionist in Belfast stating that two Belfast men named McMahon and Boyd who were serving with the Scottish Medical unit have been captured by the rebel troops in Madrid. Press reports this morning give similar information. May I request you to use your influence as early as possible with the object of ensuring the safety of these British nationals? The state of affairs in Madrid appears at the moment to be such as to cause the greatest concern for these men and I hope, therefore, that it will be possible for early action to be taken to intervene on their behalf. Yours sincerely, General Secretary. 292/946/10/62